PENINGKATAN KUALITAS HARD SKILL DAN SOFT SKILL MELALUI PENGEMBANGAN PROGRAM TEACHING FACTORY (TEFA) DI SMK MODEL PGRI 1 MEJAYAN - Yunny Erlia Putri; Elva Nuraina; Farida Styaningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This study aims to analyze the application of teaching factory program (TEFA) in improving the quality of hard skills and soft skills. This research uses descriptive qualitative research methods. This research was conducted with supported interview and documentation methods related to the teaching factory program (TEFA) at SMK Model 1 Mejayan PGRI in 2018/2019 Academic Year. The results of the study stated that there was an increase in hard skills and soft skills needed through character building, the potential of student or teacher HR, interactions between teachers and students, students and students, students and parents, self-control, and business spirit.Keywords: hard skill , soft skill, Teaching Factory (TEFA)